Islamic Fintech and Financial Inclusion: Bridging the Gap in the Digital Economy - Lina Maulidiana; Rika Santina; Adriansyah Kartadinata (Journal of Islamic Economy, 2026)
The rapid expansion of digital financial services has reshaped the global discourse on financial inclusion, yet more than a billion adults, a large share of them in Muslim-majority countries, remain excluded from formal financial systems, partly because conventional products conflict with Shariah principles. Islamic fintech has emerged as a strategic instrument that merges religious compliance with digital innovation to close this gap. This article synthesizes recent literature (2023-2026) on the relationship between Islamic fintech and financial inclusion within the digital economy, drawing on peer-reviewed studies indexed through Google Scholar and Consensus databases. Using a qualitative narrative-review method structured around identification, screening, eligibility, and synthesis stages, the study maps the instruments, drivers, and barriers shaping Islamic fintech adoption, including digital sharia banking, peer-to-peer sharia financing, digital zakat and waqf platforms, and blockchain-based instruments. The findings show that regulatory harmonization, Shariah governance, digital literacy, and public trust are decisive determinants of inclusion outcomes, while unresolved fiqh muamalah issues and infrastructural gaps in rural regions remain persistent obstacles. The article contributes an integrative framework linking maqāṣid al-Sharīʿah with digital financial inclusion indicators and offers policy implications for regulators, Islamic financial institutions, and fintech developers seeking equitable digital economic participation.